Residual cyst with a misleading clinical and radiological appearance - Najwa Karam; Fawzi Karam; Ibrahim Nasseh; Marcel Noujeim (Wolters Kluwer Medknow Publications, 2013)
A case report of a 45-year-old male who presented with a deep defect in the alveolar crest at the buccal side of the upper right 1 st molar strongly suggesting a perforation of the floor of the maxillary sinus and an oro-antral communication. Clinical signs and symptoms supported this diagnosis. After radiographic evaluation with Cone Beam Computed Tomography (CBCT), the diagnosis was shifting away from oro-antral communication. The diagnosis of a residual cyst was established after surgical exploration and removal, and histopathologic evaluation. The maxillary sinus membrane was intact.